2014
DOI: 10.1016/j.suscom.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of wasted energy in a volunteer computing system through Reinforcement Learning

Abstract: (2014) 'Reduction of wasted energy in a volunteer computing system through Reinforcement Learning.', Sustainable computing : informatics and systems., 4 (4). pp. 262-275. Further information on publisher's website:http://dx.doi.org/10.1016/j.suscom.2014.08.014Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Sustainable Computing: Informatics and Systems. Changes resulting from the publishing process, such as peer review, editing, correctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 20 publications
0
19
1
Order By: Relevance
“…These patterns are, however, quite complicated hence we evaluate the use of Reinforcement Learning in order to determine when and where jobs should be allocated within the institution in order to minimise the number of evictions and minimise the energy consumption. Through this work we have shown that it is possible to save up to 53% of the wasted energy within an institution [26].…”
Section: Prior Use Of Htc-simmentioning
confidence: 91%
See 1 more Smart Citation
“…These patterns are, however, quite complicated hence we evaluate the use of Reinforcement Learning in order to determine when and where jobs should be allocated within the institution in order to minimise the number of evictions and minimise the energy consumption. Through this work we have shown that it is possible to save up to 53% of the wasted energy within an institution [26].…”
Section: Prior Use Of Htc-simmentioning
confidence: 91%
“…These may include random allocation, lowest energy consumption, least chance of eviction, or fastest resource. Further discussion of these policies can be found in [25], [26].…”
Section: E Policy Decisions -Htcmentioning
confidence: 99%
“…The HTC system must select the most appropriate candidates from a selection of avialable resources, in order to optimise the required performance, energy and QoS metrics. Many approaches exist including random allocation, reduced energy consumption, reduced likelihood of eviction, or fastest execution time [56,57,58] -discussed further in Section 5.5. The Pluggable Policy interface provides a simple interface which a developer can use to implement their own scheduler.…”
Section: Pluggable Policy Framework Examplesmentioning
confidence: 99%
“…When considering the HTC workload, we may observe that the offered workload to our system in 2010 results in very low system utilisation (12%). BECK BRAE BRIG CHART DENE ELDON FAYOL FELL GATE GILL GLOBE HULL ISAAC LAKE LAWN LINN LOCH MOSS NAIAD NEREID NIDD ORACLE PARK PETH POND POOL SIDE TARN TEES TREE TURF TYNE WEAR WOOD Figure 8 shows the probability that a job of length x hours will complete given that it is submitted during hour y of the day [57]. Probabilities are obtained through simulation based on our Newcastle University trace logs for interactive users, and knowledge of computer reboots.…”
Section: Preparation Of the Htcondor Logsmentioning
confidence: 99%
“…Request permissions from permissions@acm.org. computers least susceptible to preemption by their primary users [20], or removing tasks which are failing to complete (due to misconfiguration or broken code) [22].…”
Section: Introductionmentioning
confidence: 99%